Transposable elements and early pregnancy in the horse - Southerland, Sierra L., author; Coleman, Stephen, advisor; Bruemmer, Jason, committee member; Fedorka, Carleigh, committee member; Pinedo, Pablo, committee member; Chicco, Adam, committee member (Colorado State University. Libraries, 2024)
Understanding the molecular events and physiological dynamics in the endometrium during early pregnancy is crucial for improving our understanding of reproductive outcomes in horses. Much of the work investigating early pregnancy in the horse has focused on maternal recognition of pregnancy (MRP). This critical signal, which initiates the pathways and regulatory changes to help make the endometrium receptive to pregnancy, remains elusive in the horse. Transposable elements (TEs), once overlooked components of the genome, have been implicated in regulating gene expression during critical stages of embryo and placental development. The current study investigated the expression of TEs during the early phase of pregnancy post-ovulation. The hypothesis tested was that pregnancy status would impact the expression patterns of TE-derived transcripts in the endometrium around the time of maternal recognition. It was anticipated that the TE transcripts would increase in the endometrium of pregnant mares either in response to or as a part of the maternal recognition signal. RNA sequencing data was generated from endometrial biopsies at days 9, 11, and 13 in pregnant and non-pregnant mares. Bioinformatics analyses identified distinct patterns of TE expression across the duration of early pregnancy. Contrary to expectations, these findings did not reveal the accumulation of TE transcripts in the pregnant endometrium compared to the non-pregnant endometrium during early pregnancy. Instead, there was a significant decrease in the number of differentially expressed transcripts over the time points studied. These results challenge the initial assumption and suggest that the regulation of TE transcriptional activity during early pregnancy may be more complex than previously thought, highlighting the need for further research into the roles of TEs in equine reproductive physiology. An alternative explanation for the results of this analysis is that maternal recognition of pregnancy may involve the downregulation of transcripts expressed from TEs, potentially serving as a switch to prevent luteolysis and maintain pregnancy. This study underscores TEs as potential biomarkers and regulators in equine reproduction, providing insights into endometrial processes and offering avenues for improving fertility outcomes and breeding efficiency in horses.